2018
DOI: 10.2478/rrlm-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular identification of carbapenemase-producing Enterobacteriaceae - challenges in diagnosis and treatment

Abstract: Introduction: Infections due to carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CPCRE) are an emerging global public health threat. The purpose of this study was to investigate phenotypic and genotypic features of CP-CRE strains isolated from hospitalized patients. Material and methods: Between 1st of January - 1st of July 2017, in the Department of Microbiology, “Dr. Constantin Opriş” County Emergency Hospital Baia Mare, Romania, 1110 strains of Enterobacteriaceae were isolated from bronchial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…In the present study the mCIM that is a new phenotypic method for detection of carbapenemases activity in CRE was positive in all 65 CP-CRE strains which is completely consistent to the result of Foldes et al, where the mCIM was positive in all 19 CP-CRE strains and no false-positive results were noticed [40]. This is also relatively consistent to Pawar et al, who reported that only one isolate which was positive by PCR study was negative by mCIM method [17], making this new method most sensitive (98.48%) among the phenotypic test studied.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study the mCIM that is a new phenotypic method for detection of carbapenemases activity in CRE was positive in all 65 CP-CRE strains which is completely consistent to the result of Foldes et al, where the mCIM was positive in all 19 CP-CRE strains and no false-positive results were noticed [40]. This is also relatively consistent to Pawar et al, who reported that only one isolate which was positive by PCR study was negative by mCIM method [17], making this new method most sensitive (98.48%) among the phenotypic test studied.…”
Section: Discussionsupporting
confidence: 92%
“…Five out of the 7 participants with urinary CPE isolates treated with monotherapy had a favourable outcome. (12)(13)(14)(15)(16)(17)(19)(20)(21). The present study did not find any strain harbouring multiple carbapenemase-encoding genes.…”
Section: Discussioncontrasting
confidence: 42%
“…In 2018 the European Centre for Disease Prevention and Control (ECDC) alerted about the emergence of resistance of CPE isolates to ceftazidime-avibactam, a newly authorized drug with activity especially against Klebsiella pneumoniae carbapenemase (KPC) producers (11). Some large Romanian medical institutions have confirmed the presence and dissemination of different types of carbapenemases (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), but the involvement of risk factors, clinical impact of CPE pathogens, treatment, and patients' outcomes have not been sufficiently explored. Furthermore, a Romanian national centralized database of circulating carbapenemase types is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of carbapenemase genes can be done either by molecular tests, which detect the presence of a resistant carbapenemase gene, or by phenotypic tests, which detect the in vitro activity of carbapenemase enzymes [ 24 , 25 ]. Molecular techniques, such as PCR, have several advantages, including accurate results and high sensitivity.…”
Section: Discussionmentioning
confidence: 99%